Public administration of higher education as a key to scientific and technological development - E. I. Shumskaya; V. D. Eremina (Вестник университета)
The article is dedicated to the pressing issue of public administration of higher education in the context of scientific and technological development. The research aim is to identify key aspects of public administration of higher education to achieve scientific and technological development goals and to propose practical recommendations for improving this interaction in Russia. The study examines the “University 3.0” concept, conducts a comparative analysis of higher education as a tool of scientific and technological development (in Russia and Israel), identifies the main problems in this area and suggests possible solutions. The study reveals the necessity to modernise the Russian higher education system in response to the challenges of scientific and technological progress. System approach, comparative analysis, methods of classification and synthesis were used during the research. The research rests on academic works of Russian and foreign authors, official websites of the legal-reference systems, as well as on statistic data published by the National Research University “Higher School of Economics”, United Nations Educational, Scientific and Cultural Organisation and the World Economic Forum.